2019
DOI: 10.3389/fenvs.2019.00040
|View full text |Cite
|
Sign up to set email alerts
|

Riparian Vegetation and Sediment Supply Regulate the Morphodynamic Response of an Experimental Stream to Floods

Abstract: Feedbacks between woody plants and fluvial morphodynamics result in co-development of riparian vegetation communities and channel form. To advance mechanistic knowledge regarding these interactions, we measured the response of topography and flow to the presence of riparian tree seedlings with contrasting morphologies in an experimental, field-scale, meandering stream channel with a mobile sand bed. On a convex point bar, we installed seedlings of Tamarix spp. (tamarisk) and Populus fremontii (cottonwood) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 76 publications
3
24
0
Order By: Relevance
“…However, velocity in the downstream direction decreased in the area close to the bed for both protected and non-protected bed conditions. The results are in good agreement with the findings of Bywater-Reyes et al [58] and Lightbody et al [59], who reported that dense configurations of vegetation alter flow velocities to a significantly greater degree than sparse or no vegetation conditions.…”
Section: Near Bed Flow Characteristicssupporting
confidence: 92%
“…However, velocity in the downstream direction decreased in the area close to the bed for both protected and non-protected bed conditions. The results are in good agreement with the findings of Bywater-Reyes et al [58] and Lightbody et al [59], who reported that dense configurations of vegetation alter flow velocities to a significantly greater degree than sparse or no vegetation conditions.…”
Section: Near Bed Flow Characteristicssupporting
confidence: 92%
“…The analysis presented here of how sediment balance (as expressed by CSR) relates to channel and floodplain geomorphic change at different time scales complements laboratory studies investigating how sediment balance mediates ecogeomorphic feedbacks. For example, Lightbody et al (2019) found that topographic change on bars was insensitive to vegetation density and morphology under sediment-deficit conditions (high CSR), in contrast to the strong influence of vegetation on deposition observed under equilibrium supply. Diehl, Merritt, et al (2017) and also documented differences in how vegetation size and morphology influenced bar-surface topography for sediment deficit versus equilibrium conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lightbody et al. (2019) found that topographic change on bars was insensitive to vegetation density and morphology under sediment‐deficit conditions (high CSR), in contrast to the strong influence of vegetation on deposition observed under equilibrium supply. Diehl, Merritt, et al.…”
Section: Discussionmentioning
confidence: 99%
“…This signifies a loss of structural complexity, a key characteristic of less anthropized systems. Vegetation has a recognized feedback on fluvial morphodynamics, influencing the patterns of sediment deposition and modifying the channel pattern toward a single-thread (Tal and Paola, 2007;Bertoldi et al, 2014;Lightbody et al, 2019). The planform changes for the studied reach of the Po River are typical of anthropogenically impacted large rivers, which usually have an oversimplified planform morphology, banks mostly covered by stable vegetation and a relatively deep main channel as a consequence of the low variability of the hydrological regime (Pettit et al, 2001;Camporeale and Ridolfi, 2006;.…”
Section: Discussion Transient Hydrology Planform Changes and Vegetation Dynamicsmentioning
confidence: 99%